2021
DOI: 10.3389/fgene.2021.672884
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and Co-expression Network Analyses Reveal Differential Gene Expression and Pathways in Response to Severe Drought Stress in Peanut (Arachis hypogaea L.)

Abstract: Drought is one of the major abiotic stress factors limiting peanut production. It causes the loss of pod yield during the pod formation stage. Here, one previously identified drought-tolerant cultivar, “L422” of peanut, was stressed by drought (35 ± 5%) at pod formation stage for 5, 7, and 9 days. To analyze the drought effects on peanut, we conducted physiological and transcriptome analysis in leaves under well-watered (CK1, CK2, and CK3) and drought-stress conditions (T1, T2, and T3). By transcriptome analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…The accumulation of activated osmotic molecular compounds and ions in plant cells may reduce osmotic potential, causing water to move into the cell, thereby increasing cell turgor to resist water deficit (Farooq et al, 2009). The main osmoregulatory substances, such as Pro, TSS, and SP, were involved in the regulation (Jadrane et al, 2020; Lin et al, 2019) and could be used as indices to evaluate drought tolerance in many plant breeding programs (Yu et al, 2017; Zhao et al, 2021). In this study, AM plants had higher Pro, TSS, and SP contents than NM plants under drought stress (Figure 5a–c).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of activated osmotic molecular compounds and ions in plant cells may reduce osmotic potential, causing water to move into the cell, thereby increasing cell turgor to resist water deficit (Farooq et al, 2009). The main osmoregulatory substances, such as Pro, TSS, and SP, were involved in the regulation (Jadrane et al, 2020; Lin et al, 2019) and could be used as indices to evaluate drought tolerance in many plant breeding programs (Yu et al, 2017; Zhao et al, 2021). In this study, AM plants had higher Pro, TSS, and SP contents than NM plants under drought stress (Figure 5a–c).…”
Section: Discussionmentioning
confidence: 99%
“…Under cold treatment, it can enhance cold tolerance and allow plants to survive [ 36 ]. After several drought stress treatments were applied to peanut plants, it was found that the expression of MAPK s was upregulated in the MAPK signalling pathway [ 37 ]. In this study, the transcription of FtMAPK1 was upregulated under hormone, drought and salt treatment, which suggested that this gene might also have important biological functions in abiotic stress and hormone signalling.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, GmNF-YC14 can interact with GmNF-YB2 and GmNF-YA16 to form a complete, active NF-Y transcriptional complex, and this complex can regulate the ABA signaling pathway mediated by the ABA receptor PYR/PYL to enhance drought resistance and salt tolerance in soybeans [ 22 ]. WGCNA, a method commonly used to identify coexpression regulatory networks, has been shown to be highly effective in many studies [ 32 ]. In this study, we used WGCNA and found that MsNF-YB2 was coexpressed with four DEAD genes in the ABA signaling pathway under salt stress, while MsNF-YB7 was coexpressed with three PP2C genes in the ABA pathway under salt stress ( Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed and constructed the weighted gene coexpression network (WGCNA) of alfalfa under salt stress using TBtools with the default parameters [ 32 , 35 ]. First, using transcriptome data (salt stress) collected at seven different time points at 0 h (CK), 0.5 h (S1), 1 h (S2), 3 h (S3), 6 h (S4), 12 h (S5), and 24 h (S6), all expressed genes were filtered based on FPKM values (more than 1) for the subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%